The effect of job resources on work engagement: A study on academicians in Turkey - Altunel, Mustafa Cevdet; Koçak, Ömer Erdem; Cankır, Bilal (Edam, 2015)
Conducting research and publishing these research papers in academic journals is an accepted norm in the academic world. Previous studies prove that work engagement is a significant predictor of performance. Herein, the relationship between work engagement, which is assumed as a substitute for performance, and job resources is examined. At least one university from each Turkish city was selected and academicians of those universities were sent a 20-item survey online. Four hundred and twenty two academicians were tested using the convenience sampling method. Job resources were subject to second-order confirmatory factor analysis. Furthermore, both for job resources and work engagement, discriminant validity, convergent validity, and composite reliability tests were conducted. The results were analyzed using structural equation modeling. The results indicate that job resources (autonomy, social support, coaching, opportunity for personal development, and task significance) need to be enhanced to develop work engagement by Turkish academicians. © 2015 EDAM.
Keywords: Autonomy; Coaching; Job Resources; Personal Growth; Social Support; Structural Equation; Work Engagement